2021
DOI: 10.1002/er.6953
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of nano spheroid‐like ZnMn2O4 materials as high‐performance anodes for lithium‐ion batteries

Abstract: Spent zinc-manganese batteries contain valuable elements, especially Zn and Mn, and recycling these metal elements can realize the sustainable development of resources. In this paper, a novel process of preparing ZnMn 2 O 4 as anode material for lithium-ion batteries from the spent zinc-manganese battery is present. Nano ZnMn 2 O 4 is synthesized by the low-temperature hydrothermal method, and the formation mechanism is discussed. The structure, morphology, and composition of the products are characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…13−15 The lower working voltage is also considered to be another advantage of ZnMn 2 O 4 when compared with cobalt-and oxide-based compounds. 16,17 However, ZMO when applied as an anode for lithium-ion batteries has huge volume changes (expansion of ∼200%) and poor kinetics during the repeated charge−discharge process. 9,18 In order to tackle the issues, researchers have developed several strategies including, nanostructuring, 19 carbon coating, 20 compositing, 10 and more.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13−15 The lower working voltage is also considered to be another advantage of ZnMn 2 O 4 when compared with cobalt-and oxide-based compounds. 16,17 However, ZMO when applied as an anode for lithium-ion batteries has huge volume changes (expansion of ∼200%) and poor kinetics during the repeated charge−discharge process. 9,18 In order to tackle the issues, researchers have developed several strategies including, nanostructuring, 19 carbon coating, 20 compositing, 10 and more.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Environmental friendliness as well as low cost are other advantages of ZMO. The spinel structure of ZMO is bivalent, where the divalent Zn ion is at the tetrahedral site, and the Mn ion which is trivalent occupies the octahedral sites. The lower working voltage is also considered to be another advantage of ZnMn 2 O 4 when compared with cobalt- and oxide-based compounds. , However, ZMO when applied as an anode for lithium-ion batteries has huge volume changes (expansion of ∼200%) and poor kinetics during the repeated charge–discharge process. , In order to tackle the issues, researchers have developed several strategies including, nanostructuring, carbon coating, compositing, and more. Kim et al reported the electrochemical performance of one-dimensional ZnMn 2 O 4 nanowires with a length of 500 nm and width of 15 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium‐ion batteries have been widely used in portable electronic devices, electric vehicles, hybrid electric vehicles, and other fields because of their high energy density, good cycle stability, and long service life 1‐5 . The cathode materials of lithium‐ion batteries play a vital role in their charge‐discharge specific capacity and voltage 6‐9 . Nowadays, commercial cathode materials for lithium‐ion batteries mainly include LiCoO 2 , LiNi x Co y Mn z O 2 , LiFePO 4 , and LiMn 2 O 4 10‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…With the popularity of wearable devices and the electric vehicle industry rising in the past few years, the demand for high‐energy‐density secondary energy storage systems has proliferated 1‐3 . Due to the lithium‐ion batteries (LIBs) system's high operating voltage, cycle life, and high energy density, it has become one of the most widely used energy storage devices 4,5 .…”
Section: Introductionmentioning
confidence: 99%